2006
DOI: 10.1177/107602960601200206
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Abnormal Biphasic aPTT Clot Waveforms in Patients with Underlying Disorders Associated with Disseminated Intravascular Coagulation

Abstract: Abnormal biphasic waveform (BPW) patterns were previously reported when the activated partial thromboplastin time (aPTT) was performed in plasma from patients with disseminated intravascular coagulation (DIC). In this study, the prevalence of the BPW was examined in a cohort of 508 hospitalized patients with elevated fibrinogen degradation products (FDP) levels (>10 microg/mL). The presence of a BPW was automatically flagged by the MDA analyzer when the slope of the precoagulation phase in the waveform exceede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 19 publications
1
60
0
1
Order By: Relevance
“…Discordance was primarily in the JMHW sensitivity to DIC in hematologic malignancies with high fibrinolytic activity. Without such patients, a further comparative study showed 93% concordance [4]. Although these were mainly in patients with infection, Gando et al found mortality to be also high in the DIC of non-infected patients diagnosed using ISTH criteria [5].…”
Section: Resultsmentioning
confidence: 99%
“…Discordance was primarily in the JMHW sensitivity to DIC in hematologic malignancies with high fibrinolytic activity. Without such patients, a further comparative study showed 93% concordance [4]. Although these were mainly in patients with infection, Gando et al found mortality to be also high in the DIC of non-infected patients diagnosed using ISTH criteria [5].…”
Section: Resultsmentioning
confidence: 99%
“…The waveform represents the change in light transmittance through a plasma specimen as the aPTT reaction takes place. The biphasic waveform is characterized by an initial steep negative slope, which is not seen in a normal waveform and is caused, in part, by precipitation of a C-reactive protein (CRP) complex [17, 18, 20]. The abnormal biphasic waveform was predictive of approximately half of fully developed DIC 18 h prior to the diagnosis provided by a battery of several other clinical tests that are currently regarded as definitive of DIC [21].…”
Section: Introductionmentioning
confidence: 99%
“…A biphasic clot waveform of APTT has been reported by some observers as an early event in DIC and noted to have an adverse outcome by others [8, 9]. …”
Section: Introductionmentioning
confidence: 99%